Dynamic Analysis of Geological Structure of Kampung Kalai, Jeli - Muhammad Fazhar Sharin (2015)
A geological research was conducted in the estate and thick forest of Kampung Kalai in kb. The objectives of this research were to conduct dynamic analysis of the geological structural settings of Kampung Kalai and to construct the geologic map of Kampung Kalai based on the orientation of the forces acquired by the analysis. A method called stereographic projection was used in utilizing trend, plunge, azimuth and dip to construct the orientation of force subjected in a locality. Laboratory analysis includes hand specimen and petrographic analysis was conducted to identify microstructure. The lithologies found in the study area are mostly transported, deposited and weathered rocks which are granite, slate, sandstone, and quartzite. Outcrops found are only schist and marble outcrop. Stereonet and contour density stereogram was generated using software from strike and dip data to depict lineation, dipping plane and distributions. The distributions are observed to predict any folding occurrences in the study area.